2015
DOI: 10.1016/j.cmet.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The Opa1-Dependent Mitochondrial Cristae Remodeling Pathway Controls Atrophic, Apoptotic, and Ischemic Tissue Damage

Abstract: SummaryMitochondrial morphological and ultrastructural changes occur during apoptosis and autophagy, but whether they are relevant in vivo for tissue response to damage is unclear. Here we investigate the role of the optic atrophy 1 (OPA1)-dependent cristae remodeling pathway in vivo and provide evidence that it regulates the response of multiple tissues to apoptotic, necrotic, and atrophic stimuli. Genetic inhibition of the cristae remodeling pathway in vivo does not affect development, but protects mice from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
342
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(364 citation statements)
references
References 57 publications
14
342
1
1
Order By: Relevance
“…[24][25][26][27] Mitochondrial dysfunction can weaken a cell's capacity to respond to a range of metabolic processes, including additional oxidative stress and fatty acid overload, and can contribute to progressive disease. 3,28 A transgenic mouse model has shown that mitochondrial dysfunction in podocytes induced by TGF-b signaling preceded the manifestation of segmental glomerulosclerosis.…”
Section: Main Findingsmentioning
confidence: 99%
“…[24][25][26][27] Mitochondrial dysfunction can weaken a cell's capacity to respond to a range of metabolic processes, including additional oxidative stress and fatty acid overload, and can contribute to progressive disease. 3,28 A transgenic mouse model has shown that mitochondrial dysfunction in podocytes induced by TGF-b signaling preceded the manifestation of segmental glomerulosclerosis.…”
Section: Main Findingsmentioning
confidence: 99%
“…Oligomerization of Opa-1, together with ATP synthase subunits e and g [10], Mitofilin and possibly every component of the "mitochondrial contact site and cristae organizing system" (MICOS) complex [11], also regulates the width of cristae junctions, connectionsites between the IMM and the cristae, where OXPHOS complexes and cytocrome-C (cytC) are localized. Thus, Opa-1 controls cytC release from the cristae during apoptosis (see Section 2.1 for details) [12,13]. Moreover, Opa-1 is a regulator of the mitochondrial quality control.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, our results indicate that stabilization of L-OPA1 and mitochondrial fusion ensures neuronal survival in the absence of PHB2, demonstrating a crucial role of OMA1 in neuronal survival in vivo. In light of our observations, it is conceivable that the protective effect of OPA1 overexpression in various mitochondrial disease mouse models Varanita et al, 2015) can be attributed to L-OPA1 only, which drives fusion and can support cell survival independently of cristae morphogenesis.…”
Section: Oma1 Cleaves Neuronal L-opa1 In Phb2 Nko Micementioning
confidence: 75%
“…Loss of OPA1 impairs mitochondrial fusion, disturbs cristae morphogenesis, and increases the apoptotic sensitivity of cells (Olichon et al, 2003;Cipolat et al, 2004;Meeusen et al, 2006). On the other hand, overexpression of OPA1 protects against apoptotic and ischemic tissue damage and ameliorates phenotypes of mitochondrial disease mouse models Civiletto et al, 2015;Varanita et al, 2015). OPA1 function is regulated by proteolytic cleavage at sites S1 and S2, which results in the balanced accumulation of noncleaved, long (L-OPA1) and cleaved, short (S-OPA1) OPA1 forms (Ishihara et al, 2006;Griparic et al, 2007).…”
Section: Introductionmentioning
confidence: 99%